Noción de cuidado en familias con un miembro con diagnóstico de trastorno afectivo bipolar (2014)
ABSTRACT: To identify the notion of care shown by the families from the psychoeducational group of Universidad de Antioquia’s Psychiatry Department who have had one of their members diagnosed with bipolar affective disorder. Methodology. To fulfill the objective, a qualitative research type was carried out having hermeneutic phenomenology as a method. During the process, in-depth interviews were carried out with 12 families, and the narratives obtained were analyzed with the qualitative Atlas-ti software. Results: Four categories emerged from the performed interviews: (i). care conceived as a good; (ii); care as a form of self-care; (iii) care as a horizontal and vertical path; and (iv) care as teleology. Conclusion. From such results, it can be concluded that families conceive care as a good that is granted to the person being cared for. In this sense, caretakers feel accomplished as long as they can provide another person with care. Therefore, this is an intersubjective practice contributing to the configuration of the identity of the two individuals involved in such care. Similarly, two possible paths were identified in regards to exercising care. Finally, care may have an immediate purpose or an underlying telos.